2007
DOI: 10.1097/01.smj.0000242793.15923.1a
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Liver Resection for Combined Biliary and Vascular Injury Following Laparoscopic Cholecystectomy: Case Report and Review of the Literature

Abstract: A 75-year-old woman suffering from symptomatic cholelithiasis was admitted to our hospital for elective laparoscopic cholecystectomy (LC). Intraoperatively, because of severe inflammation and dense adhesions in the region of the Calot triangle and bleeding arising from the porta hepatis which obscured the operating field, the method was converted to a conventional open approach. Copious hemostasis was achieved using sutures, clips and diathermy, and no bile duct or vascular injuries were recognized intraoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…Extreme vasculobiliary injuries comprise a small percentage of all vasculobiliary injuries. A recent analysis of the literature 1 identified 25 patients with such injuries, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] accounting for about 10% of all vasculobiliary injuries reported in the literature. 1 This figure corresponds closely to the incidence of 8% estimated in this paper.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extreme vasculobiliary injuries comprise a small percentage of all vasculobiliary injuries. A recent analysis of the literature 1 identified 25 patients with such injuries, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] accounting for about 10% of all vasculobiliary injuries reported in the literature. 1 This figure corresponds closely to the incidence of 8% estimated in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…The uncommon type of vasculobiliary injury involves a bile duct(s) and the proper hepatic artery, the common hepatic artery, the main portal vein, the right portal vein, or one of these veins as well as a hepatic artery, possibly including the right hepatic artery 1 . A recent review 1 identified 25 such patients in the literature 4–18 . The consequences of such injuries are much more extreme.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Right hepatic artery VBI is by far the most common VBI. In combination, the papers reviewed for this article describe about 225 patients, 92% of whom had a VBI involving the RHA 3,5,6,25–50 . The remainder involved other arteries, the portal vein alone or the portal vein in combination with arteries, and sometimes included the RHA.…”
Section: Right Hepatic Artery Vbimentioning
confidence: 99%
“…Transplantation for iatrogenic biliary injury can be performed acutely but is usually done because of a devastating combined vascular and biliary injury (Felekouras et al, 2007;Zaydfudim et al, 2009). Only rarely does secondary biliary fibrosis resulting from longstanding biliary obstruction progress to true cirrhosis (see Chapter 97A).…”
Section: Liver Transplantationmentioning
confidence: 99%